2021
DOI: 10.1074/jbc.ra120.015502
|View full text |Cite
|
Sign up to set email alerts
|

KDM2B is involved in the epigenetic regulation of TGF-β-induced epithelial–mesenchymal transition in lung and pancreatic cancer cell lines

Abstract: Polycomb repressive complex-1 (PRC1) induces transcriptional repression by regulating monoubiquitination of lysine 119 of histone H2A (H2AK119) and as such is involved in a number of biological and pathological processes including cancer development. Previously we demonstrated that PRC2, which catalyzes the methylation of histone H3K27, has an essential function in TGF-β-induced epithelial–mesenchymal transition (EMT) of lung and pancreatic cancer cell lines. Since the cooperative activities of PRC1 and PRC2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…As such, these cell lines have been used to study different aspects of pancreatic cancer, including DNA methylation, RNA splicing, histone modification, EMT, TGFβ signaling, and anticancer drug testing. [154][155][156][157] Results from these studies have shown correlations between gene expression, activation of specific cellular pathways, and drug response. In particular, the expression of MUC1 was found to induce drug resistance through the upregulation of multidrug resistance genes.…”
Section: Established (Commercial Cell Lines)mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these cell lines have been used to study different aspects of pancreatic cancer, including DNA methylation, RNA splicing, histone modification, EMT, TGFβ signaling, and anticancer drug testing. [154][155][156][157] Results from these studies have shown correlations between gene expression, activation of specific cellular pathways, and drug response. In particular, the expression of MUC1 was found to induce drug resistance through the upregulation of multidrug resistance genes.…”
Section: Established (Commercial Cell Lines)mentioning
confidence: 99%
“…Their availability increase research efforts in the field of cancer research. As such, these cell lines have been used to study different aspects of pancreatic cancer, including DNA methylation, RNA splicing, histone modification, EMT, TGFβ signaling, and anticancer drug testing 154–157 . Results from these studies have shown correlations between gene expression, activation of specific cellular pathways, and drug response.…”
Section: Late Diagnosismentioning
confidence: 99%
“…4); очень редко, по одному случаю в каждой группе, обнаруживалась экспрессия десмина в единичных группах клеток. Миофибробласты являются главным стромальным компонентом и прогностическим маркером многих опухолей [8,9]. Они секретируют цитокины, протеазы и матриксные белки, обнаруживаются чаще в инвазивном крае опухоли [8,10].…”
Section: результаты и обсуждениеunclassified
“…Миофибробласты являются главным стромальным компонентом и прогностическим маркером многих опухолей [8,9]. Они секретируют цитокины, протеазы и матриксные белки, обнаруживаются чаще в инвазивном крае опухоли [8,10]. Ответственными за трансдифференцировку фибробластов в миофи-бробласты является трансформирующий фактор роста β (ТGF β), один из экстрацеллюлярных сигналов, индуцирующих ЭМТ [11,12].…”
Section: результаты и обсуждениеunclassified
“…In addition, epigenetic regulations are considered as one of the critical mechanisms for EMT owing to its phenotypic plasticity ( 5 , 6 ). Thus, we have investigated and found the essential roles of histone methylation, histone ubiquitination, and long noncoding RNAs in the transcriptional regulatory network during EMT ( 7 , 8 , 9 , 10 ).…”
mentioning
confidence: 99%